2016
DOI: 10.6007/ijarbss/v6-i7/2249
|View full text |Cite
|
Sign up to set email alerts
|

Job Satisfaction as an Intervening Variable of Self-Efficacy and Employee Performance

Abstract: This study examined the effects of self-efficacy, empowerment and organizational culture on job satisfaction and employee performance employees, as well as test the mediating effect of variables Job Satisfaction. The sample in this study was 120 employees of PT. Surya Madistrindo Branch Lhokseumawe. The analytical tool used is path analysis by SEM method (Structural Equation Modeling) using AMOS. The results showed that each variable empowerment, selfefficacy and organizational culture positive and significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 1 publication
1
3
0
Order By: Relevance
“…7) The seventh hypothesis was rejected, because although the strategy direction proved to affect the operation performance but human resource management had no effect on the operation performance. This research provides an overview of the possibility to parse the human resource management variables into variables with a more limited scope in accordance with the results of previous research showed that human resource management when measured using compensation (Aji, et al, 2017) and when measured using job satisfaction (Iis & Mukhlis, 2014) can be used as a intervening variable.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…7) The seventh hypothesis was rejected, because although the strategy direction proved to affect the operation performance but human resource management had no effect on the operation performance. This research provides an overview of the possibility to parse the human resource management variables into variables with a more limited scope in accordance with the results of previous research showed that human resource management when measured using compensation (Aji, et al, 2017) and when measured using job satisfaction (Iis & Mukhlis, 2014) can be used as a intervening variable.…”
Section: Discussionsupporting
confidence: 78%
“…7) The results of previous research showed that human resource management when measured using compensation (Aji, et al, 2017) and when measured using job satisfaction (Iis & Mukhlis, 2014) can be used as an intervening variable. H7: Human resource management as a moderator between strategy direction and operation performance.…”
Section: Hyphothesesmentioning
confidence: 99%
“…Additionally, numerous researchers argue that job satisfaction among employees acts as a mediating variable through various antecedent variables, affecting subsequent variables, and have confirmed its mediating effects (Colakoglu et al, 2010;Iis & Yunus, 2016). Based on this, the current study also proposes the following hypotheses to investigate the mediating effect of mindfulness and job satisfaction (Figure 1): Hypothesis 7.…”
Section: Hypotheses Developmentmentioning
confidence: 63%
“…Therefore, many scholars have applied mindfulness as a mediating variable in the relationship between various variables (Ampofo, 2020; Javaid et al, 2023; Said & Tanova, 2021; Vinothkumar et al, 2016). Additionally, numerous researchers argue that job satisfaction among employees acts as a mediating variable through various antecedent variables, affecting subsequent variables, and have confirmed its mediating effects (Colakoglu et al, 2010; Iis & Yunus, 2016). Based on this, the current study also proposes the following hypotheses to investigate the mediating effect of mindfulness and job satisfaction (Figure 1):Hypothesis Mindfulness has a mediating impact on the relationship between job stress and quality of life.Hypothesis Mindfulness has a mediating impact on the relationship between job satisfaction and quality of life.…”
Section: Literature Reviewmentioning
confidence: 97%